Problematyka wolności sumienia w świetle współczesnych wyzwań - Machinek, Marian (Collectanea Theologica, 2016)
In the first section the article presents the three main dimensions of conscience. There is no doubt that the primary dimension is the dimension of individual conscience. It is the “guardian of the integrity of” moral person (E. Fromm). It is so closely associated with the self-consciousness of people that acting against the judgment of conscience, a man acts against himself. Conscience is also “a window on what is common” (Joseph Ratzinger), to moral truth, what is the revelation of the objective dimension of conscience. Finally, it is important religious dimension. It manifests itself in defining conscience as the voice of God. In the second section the author analyzes the key element of the contemporary dispute about conscience that is his relationship to authority, both the state and the church. There is no doubt that state law should respect the freedom of conscience of citizens and, in situations of serious conflicts – provide the opportunity to invoke the conscience clause. In contrast to the pluralistic society ecclesial community has the right to have moral convictions stemming form faith, which are crucial to belong to the individual religious community. This does not invalidate in any way the importance of conscience, which remains the final court (although not the highest standard, which is God) of moral action.